(untitled) (Comprehensive Journal of Science, 2025)
The presence of hydrogen sulfide in the workplace is unsafe, as it poses a significant risk to worker and environmental safety when exposure limits exceed maximum levels. This study aimed to monitor and measure the concentration and spread of this gas in the workplace and determine the most significant health effects on workers. The study focused on two main aspects. The first involved measuring hydrogen sulfide concentrations in all departments of the company under study using specialized equipment. The second included a questionnaire surveying employees about health problems associated with the presence of this gas in workplaces. The correlation coefficient between health problems and employees’ personal factors was also determined. The study results showed that the concentration of H2S gas in all work sites falls within the internationally permitted limits, according to OSHA specifications. However, long-term exposure to these levels causes serious damage, as the highest concentration levels of H2S gas in some work sites reached (3 ppm). The most common health problems identified in the study were headaches, coughing, eye irritation, and loss of smell, with rates of 35%, 10%, 10%, and 9.7%, respectively. The age group most affected by headaches was the 31-43 age group. Workers with high levels of education were also more likely to report experiencing health problems. Workers with 5-9 years of service are more likely to suffer from health problems, while technicians recorded the highest number of workers with health problems. The permissible limits according to Occupational Safety and Health Administration (OSHA) specifications are within the limits. Correlation coefficient results also showed that most health problems are strong or moderately related to the nature of the job.